Bridging the gap between policy and practice: Unpacking the commercial rhetoric of Google for Education. (July 2022) - Carlsson, Hanna
This paper unpacks the commercial rhetoric of Google for Education . Through the analysis of information published on the official Google for Education website, the paper seeks to make visible how this service promotes and reproduces certain ways of talking, thinking about and doing education. The aim is to contribute to a critical discussion of the potential implications of allowing major commercial players to take the lead in the development of digital infrastructure in education. Guiding the analysis is the notion of 'problem' understood as central for Google for Education 's success story. The case of Sweden, in which Google for Education has become widely used, forms the vantage point for this discussion. The study makes visible how Google for Education, in the commercial rhetoric, is constructed as the solution to problem representations by being positioned as a much-needed bridge, in the shape of digital information infrastructure, between digital policy and educational practice. However, Google for Education is far from simply a practical solution to a set of expensive and urgent problems. To uncritically embrace Google as the information infrastructure of education is to hand over power to one actor, which closes doors to alternative paths of doing and knowing in education.